2022
DOI: 10.1136/neurintsurg-2021-018312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sine Spin flat detector CT imaging compared with multidetector CT

Abstract: BackgroundFlat detector computed tomography (FDCT) is widely used for periprocedural imaging in the angiography suite. Sine Spin FDCT (SFDCT) is the latest generation of cone beam CT using a double oblique trajectory for image acquisition to reduce artefacts and improve soft tissue brain imaging. This study compared the effective dose, image quality and diagnostic performance of the latest generation of SFDCT with multidetector CT (MDCT).MethodsAn anthropomorphic phantom equipped with MOSFET detectors was used… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…7 The resulting series of images is backprojected to produce a volumetric dataset. 8 9 Newer machines, destined to soon become the standard, use acquisition obtained with alternative techniques compared with the traditional circular one, named sine spin 10 or dual-axis butterfly 11 Manufacturers offer different CBCT acquisition protocols that are targeted and optimized for certain clinical tasks. The acquisition protocols can differ in several basic parameters such as beam kVp, focal spot size, maximum X-ray pulse length, number of frames acquired per degree of rotation, dose per frame, number of pixels acting as detection unit, field of view (FOV), and presence of a 'mask' or background image.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The resulting series of images is backprojected to produce a volumetric dataset. 8 9 Newer machines, destined to soon become the standard, use acquisition obtained with alternative techniques compared with the traditional circular one, named sine spin 10 or dual-axis butterfly 11 Manufacturers offer different CBCT acquisition protocols that are targeted and optimized for certain clinical tasks. The acquisition protocols can differ in several basic parameters such as beam kVp, focal spot size, maximum X-ray pulse length, number of frames acquired per degree of rotation, dose per frame, number of pixels acting as detection unit, field of view (FOV), and presence of a 'mask' or background image.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…The role of HR-CBCT in dural arteriovenous fistula (dAVF) has been demonstrated already in multiple articles and it is currently used by many groups. 19 20 One obvious reason to prefer CBCT to 3D-DSA is to understand the angioarchitecture of the fistula in more detail, namely the vessels supplying it and adjacent dangerous anastomoses (figures [10][11]. A careful evaluation of the images provided may lead to identification of the venous pouch which can be superselected as a venous target.…”
Section: Cranial Dural Arteriovenous Fistulamentioning
confidence: 99%
See 1 more Smart Citation
“…83 Another study that compared the latest CBCT technology with NCCT showed that early ischemic lesions were detected with a sensitivity of 73.3% and specificity of 94.7%, when compared with NCCT. 84 Further refinements in the x ray tube trajectory to include caudal and cranial angulations have decreased artifacts. 85 Novel motion correction algorithms to improve imaging quality and diagnostic assessment of the brain parenchyma have been implemented.…”
Section: Utility Of Cone Beam Computed Tomographymentioning
confidence: 99%
“…While previous studies have explored the role of CBCT in interventional procedures [ 3 , 6 , 10 ], there has been limited research specifically focusing on the radiation dose associated with CBCT image acquisition. Some studies have employed phantoms to estimate the dose of CBCT, but the corresponding results have shown significant variations due to the different methodologies used for estimating the effective dose (ED) [ 12 , 13 , 14 , 15 , 16 , 17 ]. Direct measurement of ED may be affected by differences in phantom size or material.…”
Section: Introductionmentioning
confidence: 99%